Using Linked Data Sources to Enhance Catalog Discovery - Khan, Huda; DeMarco, Claire; Fernsebner Eslao, Christine; Folsom, Steven; Kovari, Jason; Warner, Simeon; Worrall, Tim; Usong, Astrid (KULA)

(untitled) (University of Victoria Libraries, 2022)
Our research explores how linked data sources and non-library metadata can support open-ended discovery of library resources. We also consider which experimental methods are best suited to the improvement of library catalog systems. We provide an overview of the questions driving our discovery experiments with linked data, a summary of some of our usability findings, as well as our design and implementation approach. In addition, we situate the discussion of our work within the larger framework of library cataloging and curation practices.